Bipolar disorder and substance abuse (Archives of Clinical Psychiatry, 2005)
The bipolar disorder and substance abuse are illness with highly autonomy limitation potential, becoming still more serious when associates. This article presents the available scientific evidences concerning the epidemiology, etiology, clinical evolution, diagnosis and pharmacological and psychosocial approaches designed for the bipolar disorder and substance abuse comorbidity.